(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Percutaneous transhepatic gallbladder drainage has been recognized by many centers as an effective method for reducing gallbladder inflammation. It is considered a temporary treatment step prior to cholecystectomy or a definitive solution for patients with multiple surgical risk factors who are not candidates for surgery. Objectives: To evaluate the outcomes of laparoscopic cholecystectomy following gallbladder drainage. Subjects and Methods: A retrospective descriptive study was conducted on 35 patients with acute cholecystitis due to gallstones who underwent laparoscopic cholecystectomy after gallbladder drainage at the Hepato-Pancreato-Biliary Surgery Department, Thong Nhat Hospital, from January 2022 to May 2024. Results: The avervage age was 71.14 ± 12.6 years. The male-to-female ratio was 1.2:1. The rate of abdominal surgical history was 11.4% of cases, and comorbidities accounted for 91.4%, with cardiovascular disease (80%) and diabetes mellitus (40%) being predominant. ASA III classification was the most common, accounting for 42.9%. 28/35 patients (80%) underwent drainage within 72 hours after diagnosis. Most patients had their drains in place for over 6 weeks (85.75%). The average operating time was 128 ± 46.5 minutes, the average blood loss was 24.3 ± 15.3 ml. Intraoperative complications occurred in 5.8%, with one case (2.9%) of major bile duct injury and one case (2.9%) of duodenal injury. Postoperative complications were observed in 5.7%, including 2 cases of bile leakage. The average postoperative length of stay was 6.5 ± 2.6 days. Conclusion: Laparoscopic cholecystectomy following percutaneous gallbladder drainage has a high success rate and low rates of perioperative complications. Gallbladder drainage is an effective, easily performed, and safe treatment for cases of acute cholecystitis that are not suitable for surgery.